PERFORMANCE OF BROILER CHICKEN PRODUCTION THAT GIVEN LEAF FLOUR KATUK (Saurapus Androginus) WITH DIFFERENT LEVELS - Sulfiar, Ahmat Endang Two; Pagala, Muhammad Amrullah; Malesi, La (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2020)
This study aimed to determine the effect of katuk leaf powder in rations on consumption, body weight gain, and ration conversion of broiler chicken.  The materials used in this research were 64-day old chicks (DOC) of broiler that were maintained for five weeks.  Chickens were divided into 16 plots of cages where each plot was filled with 4 chicken experiments. This study used a completely randomized design consisted of four treatments and four replications. The treatments were control (P0), level of 2% of katuk leaf powder (P1), level of 4 % of katuk leaf powder (P2), and level of 6% of katuk leaf powder (P3).  Parameters observed were feed consumption, body weight gain, and feed conversion. The result showed that the addition of katuk leaf powder in the ration of each treatment gave the same amount of consumption.  The level of 2% of katuk leaf powder could improve the weight gain of broiler chicken